HPV Game: Alleviates Vaccine Hesitancy Among High School Students Through Edutainment Gaming - Mohd Azrul Hisham, Mohd Adib (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Introduction: Cervical cancer ranks as the third most common cancer among women in Malaysia. Therefore, there is a great need to increase the prevention of the disease through HPV (Human Papillomavirus) vaccination among adolescents. However, the Malaysian Ministry of Health encounter vaccine hesitancy issues among Malaysian youths. The possible factors for reduced vaccine uptakes among high school students were due to lack of awareness and vaccine hesitancy. Objective: This study aims to alleviate vaccine hesitancy among high school student by creating awareness towards cervical cancer, and to promote the HPV vaccines uptake among high school students by using edutainment gaming known as “HPV Game”.